The costume making guide : creating armor & props for cosplay - Quindt, Svetlana (Impact, 2016)
"Packed with more than 30 step-by-step demonstrations that teach the skills you need to bring all your favorite characters to life no matter the genre, Kamui Cosplay deconstructs the work that goes into making a complete costume, from the first thought to the final photo. Tutorials cover design planning, fabricating body armor, 3D painting techniques and more. Best of all, you can adapt every lesson to use in all future fandom projects spanning video games, books, anime, movies and even your own original characters!"--amazon.com.